Assessment of littoral algal diversity from the northern Gulf of Mexico using environmental DNA metabarcoding. Issue 1 (7th December 2020) - Bombin, Sergei; Wysor, Brian; Lopez‐Bautista, Juan M.
Abstract : Traditional methods for algal biodiversity monitoring are costly and time inefficient because they rely on high‐level taxonomic expertise to address species identity problems involving phenotypic plasticity and morphological convergence. These problems are exacerbated in regions such as the Gulf of Mexico, that has a limited history of phycological exploration, but that are economically important or threatened by numerous anthropogenic stressors. Given the high pace of disturbance to natural systems, there is a critical need for expedient and cost‐effective tools for the study of benthic algal communities. Here we document the use of environmental DNA metabarcoding, using the partial LSU rDNA and 23S rDNA plastid molecular markers, to elucidate littoral algal diversity in the Northern Gulf of Mexico. We assigned 73.7% of algal OTUs to genus and 59.6% to species ranks. Our current study detected molecular signals for 35 algal/protist species with no previous reports in the Gulf of Mexico, thus providing an important, molecular‐validated, baseline of species richness for this region. We also make several bioinformatic recommendations for the efficient use of high‐throughput sequence data to assess biological communities.